Reactions of saturated NHC·boranes with electron-deficient alkynes and alkenes. borirane formation, their reactivities, and coupling of tetracyanoethylene - Amrutha, P. R.; Kundu, Gargi; Ganesh, Vemuri Lakshmi; Gonnade, Rajesh G.; Gopakumar, Gopinadhanpillai; Sen, Sakya S. (Dalton Transactions, 2026)
In this study, we describe the reactions of five- and six-membered saturated N-heterocyclic carbene boranes (NHC & centerdot;BH3) with electron-deficient alkenes and alkynes. Notably, both five- and six-membered saturated NHCs form boriranes upon the reaction of NHC & centerdot;BH3 with dimethyl acetylene dicarboxylate (DMAD). However, their reactivity with HCl differs: the five-membered saturated NHC-stabilized borirane undergoes ring opening in toluene/THF, whereas the six-membered saturated NHC-stabilized borirane undergoes ring expansion, forming exclusively a boralactone irrespective of solvent. Interestingly, when acetonitrile is used as a solvent, the five-membered saturated NHC-stabilized borirane yields both ring-opening and ring-expansion products. To remove the hydrogen attached to the boron atom in boriranes, we reacted the five-membered saturated NHC-stabilized borirane with AlCl3 and B(C6F5)(3), resulting in azaborolium cation or adduct formation, respectively. Transitioning from an electron-deficient alkyne to an alkene, the reaction of six-membered saturated NHC & centerdot;BH3 with tetracyanoethylene (TCNE) led to the unusual coupling of two TCNE molecules.